Lead Selection of a New Aminomethylphenol, JPC-3210, for Malaria Treatment and Prevention - Chavchich, Marina (Antimicrob Agents Chemother, 2016)
Structure-activity relationship studies of trifluoromethyl-substituted pyridine and pyrimidine analogues of 2-aminomethylphenols (JPC-2997, JPC-3186, and JPC-3210) were conducted for preclinical development for malaria treatment and/or prevention. Of these compounds, JPC-3210 [4-(tert-butyl)-2-((tert-butylamino)methyl)-6-(5-fluoro-6-(trifluoromethyl)pyridin-3-yl)phenol] was selected as the lead compound due to superior in vitro antimalarial activity against multidrug-resistant Plasmodium falciparum lines, lower in vitro cytotoxicity in mammalian cell lines, longer plasma elimination half-life, and greater in vivo efficacy against murine malaria.